Synaptic determinants of cholinergic interneurons hyperactivity during parkinsonism - Padilla-Orozco, Montserrat; Duhne, Mariana; Fuentes-Serrano, Alejandra; Ortega, Aidán; Galarraga, Elvira; Bargas, José; Lara-González, Esther (Frontiers in Synaptic Neuroscience, 2022)
Parkinson’s disease is a neurodegenerative ailment generated by the loss of dopamine in the basal ganglia; mainly the striatum. The disease courses with increased striatal levels of acetylcholine disrupting the balance between these modulatory transmitters. These modifications disturb the excitatory and inhibitory balance in the striatal circuitry as reflected in the activity of projection striatal neurons. In addition, changes in the firing pattern of striatal tonically active interneurons during the disease, including cholinergic interneurons, are being searched. Dopamine depleted striatal circuits exhibit pathological hyperactivity as compared to controls. One aim of this work is to show how striatal cholinergic interneurons contribute to this hyperactivity. A second aim is to show the contribution of extrinsic synaptic inputs onto striatal cholinergic interneurons hyperactivity. Electrophysiological and calcium imaging recordings in Cre-mice allowed us to evaluate the activity of dozens of identified cholinergic interneurons with single-cell resolution in ex-vivo brain slices. Cholinergic interneurons show a hyperactivity with bursts and silences in dopamine depleted striatum. We confirmed that intrinsic differences between the activity of control and dopamine depleted cholinergic interneurons are one source of their hyperactivity. We also show that a great part of this hyperactivity and firing pattern change is a product of extrinsic synaptic inputs targeting cholinergic interneurons. Both glutamatergic and GABAergic inputs are essential to sustain hyperactivity. In addition, cholinergic transmission through nicotinic receptors also participates, suggesting that the joint activity of cholinergic interneurons drives the phenomenon; since striatal cholinergic interneurons express nicotinic receptors, not expressed in striatal projection neurons. Therefore, cholinergic interneurons hyperactivity is the result of changes in intrinsic properties and in excitatory and inhibitory inputs, in addition to the modification of local circuitry due to cholinergic nicotinic transmission. We conclude that cholinergic interneurons are a main drive of the pathological hyperactivity present in the striatum depleted of dopamine and that this is in part a result of extrinsic synaptic inputs. These results show that cholinergic interneurons may be a main therapeutic target to treat Parkinson’s disease by intervening their synaptic inputs.